Analysing EMIS data: The case of Afrikaans - Kirchner, Emma (Journal for Studies in Humanities and Social Sciences, 2015)
Since Independence Afrikaans lost its status as official language. However, it is still used as lingua franca in parts of the country. In some schools Afrikaans is used as medium of instruction and also offered as a subject from grade 1 to 12. The purpose of this presentation is to analyse enrolment data regarding Afrikaans as captured in the Education Management Information System of the Ministry of Education in Namibia. An attempt will be made to ascertain whether any patterns regarding the enrolment of Afrikaans first and second language can be found. In conclusion, some remarks on the future of Afrikaans as school subject, also set against the proposals for a revised language policy for schools, will be made. EMIS is a useful tool that could be used by researchers and educationalists to document and discuss developments in the education sector, e.g. enrolment, teacher qualifications and physical facilities.